2021
DOI: 10.3390/nu13051487
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intakes of Recipients of Faecal Microbiota Transplantation: An Observational Pilot Study

Abstract: This study reports on the dietary intake of recipients of faecal microbiota transplantation (FMT), comparing this with dietary guidelines, and investigates the relationship between dietary intake and clinical outcomes. Males and females aged ≥ 16 years with irritable bowel syndrome or inflammatory bowel disease undergoing FMT were invited to complete validated symptom and quality of life (QOL) questionnaires and three-day weighed food diaries. Descriptive statistics were calculated for symptom scores, QOL scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…For example, as fecal microbiota transplantation (FMT) becomes more widely used, the ability of diet to modify the microbiota has also been appreciated. 17 Registered dietitians (RDs) could play an integral role by working with patients who have undergone FMT to sustain the newly colonized gut and provide education on appropriate foods for an improved outcome. RDs should be aware of FMT and be prepared to provide suitable interventions.…”
Section: T He Incidence Of Chronic Disease Is a Growingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as fecal microbiota transplantation (FMT) becomes more widely used, the ability of diet to modify the microbiota has also been appreciated. 17 Registered dietitians (RDs) could play an integral role by working with patients who have undergone FMT to sustain the newly colonized gut and provide education on appropriate foods for an improved outcome. RDs should be aware of FMT and be prepared to provide suitable interventions.…”
Section: T He Incidence Of Chronic Disease Is a Growingmentioning
confidence: 99%
“…For example, fiber intake has been identified as a means of managing intestinal diseases and preventing flareups. Clancy and colleagues 17 explored the relevance of dietary intake of fiber, according to the dietary guidelines, to patients with irritable bowel syndrome and inflammatory bowel disease (IBD) who received FMT. RDs assessed participants' food diaries and it was determined that these FMT patients had higher intake of fiber than the population average.…”
Section: Influence Of Fmt On Public Health and Dietetics Practicesmentioning
confidence: 99%
“…Pilot studies examining the relationship between recipient fibre intake and FMT outcomes have demonstrated a positive trend ( 13 , 14 ), a study by Wei et al compared the outcomes of UC patients receiving FMT and a known prebiotic fibre (pectin) supplement or FMT alone. Their results suggested that supplementation with pectin delayed the loss of diversity of transplanted gut microbiota and enhanced the effects of the FMT ( 15 ).…”
Section: Introductionmentioning
confidence: 99%